Strengthening Judicial Authority In Sharia Economic Disputes: A Legal Study Of Indonesia’s Religious Courts - Ridwan Malik; M. Thahir Maloko; Fatmawati Fatmawati (Universitas Muhammadiyah Makassar, 2025)
This study explores the legal and institutional dynamics of Sharia economic dispute resolution in Indonesia by analyzing the impact of Law No. 3 of 2006 and Law No. 50 of 2009 on the jurisdiction and functioning of the Religious Courts. In response to the rapid growth of Islamic finance, the study investigates how Indonesia's judiciary has adapted to accommodate Sharia-based commercial transactions. Using a normative-juridical approach and library-based legal research, the study evaluates primary legislation, court rulings, and relevant scholarly discourse. The findings show that Law No. 3 of 2006 significantly redefined the role of Religious Courts by formally granting them the authority to adjudicate Sharia economic disputes. Law No. 50 of 2009 further enhanced legal clarity and institutional capacity, thus fostering a supportive environment for Islamic finance. Despite these advancements, the implementation process faces persistent challenges. These include inadequate judicial training, underutilization of alternative dispute resolution methods, and procedural inconsistencies. The study also notes a lack of public trust in Religious Courts and insufficient integration between Sharia principles and national legal standards. The study concludes that while statutory reforms have laid a robust foundation comprehensive institutional and procedural adjustments are essential for ensuring legal certainty and promoting the legitimacy of Sharia economic dispute resolution. This research contributes to the growing discourse on Islamic legal reform and offers policy-relevant insights for harmonizing religious and national legal systems in pluralistic societies.